2014
DOI: 10.1175/jcli-d-13-00365.1
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Patterns of the ENSO Signal in Africa over the Last 30 Years: Insights from Normalized Difference Vegetation Index Data

Abstract: A more complete picture of the timing and patterns of the ENSO signal during the seasonal cycle for the whole of Africa over the three last decades is provided using the normalized difference vegetation index (NDVI). Indeed, NDVI has a higher spatial resolution and is more frequently updated than in situ climate databases, and highlights the impact of ENSO on vegetation dynamics as a combined result of ENSO on rainfall, solar radiation, and temperature.The month-by-month NDVI-Niño-3.4 correlation patterns evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 86 publications
(85 reference statements)
9
29
1
Order By: Relevance
“…Hereby, infiltration to the soil reservoir is minor, since most of the water is lost due to immediate surface run-off [36]. What is more, the timing of rainfall deficits is decisive for the occurrence of vegetative stress and the associated decrease in VCI.…”
Section: Comparison Of Spi-3 and Vcimentioning
confidence: 99%
See 2 more Smart Citations
“…Hereby, infiltration to the soil reservoir is minor, since most of the water is lost due to immediate surface run-off [36]. What is more, the timing of rainfall deficits is decisive for the occurrence of vegetative stress and the associated decrease in VCI.…”
Section: Comparison Of Spi-3 and Vcimentioning
confidence: 99%
“…This was revealed from observed droughts during La Niña phases that coincide with respective growing seasons (see Figure 10). However, Philippon et al [36] suggested a remarkably weaker effect of ENSO for the secondary, compared to the first growing season, based on long-term analysis of NDVI and its sensitivity to ENSO. In the present study, drought signals were observed over central Ethiopia, Uganda and western Kenya in the ongoing stage of El Niño, prior to the phase of highest ENSO intensity (see Figures 8 and 9).…”
Section: Spatio-temporal Variability Of Agricultural Droughts During mentioning
confidence: 99%
See 1 more Smart Citation
“…Since these ecosystem services are essential, evaluating the environmental controls that modulate GPP dynamics is necessary for accurate accounting of primary productivity. The Sahel has a single growing season that starts in July and ends in October [9] with considerable inter-annual variability in the spatial distribution and quantity of rainfall [10,11]. The driest parts of the northern Sahel receive an annual average of 150 mm of rain, while the southern parts receive an annual average of ~750 mm [12] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Our basis is the bias-corrected July to October satellite vegetation fraction (NDVI) from 1982 to 2014 (Huete et al, 2002;Tucker et al, 2005;Philippon et al, 2014) averaged over the Ethiopian highlands (box in Figure 1a). Atmosphere and ocean reanalysis fields are studied for patterns both simultaneously and in precursor season.…”
Section: Datas and Methodsmentioning
confidence: 99%